2016
DOI: 10.1088/0953-8984/29/3/035802
|View full text |Cite
|
Sign up to set email alerts
|

Collinear antiferromagnetism in trigonal SrMn2As2revealed by single-crystal neutron diffraction

Abstract: Iron pnictides and related materials have been a topic of intense research for understanding the complex interplay between magnetism and superconductivity. Here we report on the magnetic structure of SrMnAs that crystallizes in a trigonal structure ([Formula: see text]) and undergoes an antiferromagnetic (AFM) transition at [Formula: see text] K. The magnetic susceptibility remains nearly constant at temperatures [Formula: see text] with [Formula: see text] whereas it decreases significantly with [Formula: see… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
33
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 39 publications
(62 reference statements)
3
33
0
Order By: Relevance
“…Single-crystal neutron diffraction measurements on trigonal SrMn 2 As 2 showed that the Mn moments are ordered in the ab plane in a collinear Néel AFM structure below T N = 118(2) K [51] and magnetic susceptibility data exhibited quasi-2D behavior at T T N [30], as does ThCr 2 Si 2 -type BaMn 2 As 2 as noted above. SrMn 2 P 2 exhibits a novel pressure-induced structural transition from the trigonal CaAl 2 Si 2 -type to the body-centered-tetragonal ThCr 2 Si 2 -type structure [58].…”
Section: Introductionmentioning
confidence: 53%
“…Single-crystal neutron diffraction measurements on trigonal SrMn 2 As 2 showed that the Mn moments are ordered in the ab plane in a collinear Néel AFM structure below T N = 118(2) K [51] and magnetic susceptibility data exhibited quasi-2D behavior at T T N [30], as does ThCr 2 Si 2 -type BaMn 2 As 2 as noted above. SrMn 2 P 2 exhibits a novel pressure-induced structural transition from the trigonal CaAl 2 Si 2 -type to the body-centered-tetragonal ThCr 2 Si 2 -type structure [58].…”
Section: Introductionmentioning
confidence: 53%
“…The χ(T ) and M (H) data suggest that the AFM structure of the Eu spins is a noncollinear, noncoplanar structure. AFM ordering of the Mn spins in EuMn 2 As 2 is inferred from the high-T χ(T ) and C p (T ) data which indicate that the Mn Néel temperature is T N = 142 K. Although our measurements yield no information on the AFM structure of the Mn spins below their T N , we note that the Mn spins in the very similar SrMn 2 As 2 compound have a collinear AFM structure with the easy axis aligned within the ab plane [50]. We see no clear evidence from M (H) isotherms between 2 and 20 K of metamagnetic transitions in EuMn 2 As 2 in fields up to 14 T.…”
Section: A Eumn2as2 and Related Compoundsmentioning
confidence: 69%
“…Both compounds are AFM semiconductors with T N = 62 K and 120 K, respectively [49,50]. A previous study of SrMn 2 As 2 single crystals found T N = 125 K [51].…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…These results are qualitatively similar to those in BaCr 2 As 2 [22] but distinctly different from those of other SrT 2 As 2 (T = Mn, Fe, Co) compounds. Specifically, SrMn 2 As 2 does not crystallize in a tetragonal I4/mmm space group but forms a trigonal lattice with collinear AFM structure [18], SrFe 2 As 2 undergoes a first order structural transition from tetragonal to an orthorhombic AFM phase at low temperatures [38] and SrCo 2 As 2 is non-magnetic with I4/mmm crystal symmetry but undergoes a pressure-induced cT phase [28]. Figure 5 shows the temperature dependence of the integrated intensity (I M ) of the (1 0 1) Bragg peak, which is a measure of the magnetic moment.…”
Section: Resultsmentioning
confidence: 99%